Immune responses in pulmonary sarcoidosis following COVID-19 - Starshinova, Anna; Kudryavtsev, Igor; Rubinstein, Artem; Akisheva, Tatiana; Golovkin, Alexey; Korobova, Zoia; Kulpina, Anastasia; Kudlay, Dmitry (Frontiers in Immunology, 2025)
Background/objectivesThe complex interplay between sarcoidosis and COVID-19 remains an important area of research, since COVID-19 leads to long-term changes in the immune system. However, COVID-19 is often followed by autoimmune diseases, including newly manifesting sarcoidosis. The goal of this study is to characterize CD4+ T cell subsets, playing a pivotal role in the regulation of innate and adaptive immunity, in the peripheral blood of patients with sarcoidosis after COVID-19.MethodsThe peripheral blood samples from patients with sarcoidosis (n = 61) were studied. We divided patients into two distinct groups: sarcoidosis patients with no history of COVID-19 (n= 30) and COVID-19 convalescent patients with sarcoidosis within 12–24 weeks after recovery (n = 31). Healthy controls (n = 40) were similar in terms of age and sex to patients with sarcoidosis. Immunophenotyping of peripheral blood cells was performed using a ten-color flow cytometry.ResultsSarcoidosis patients with COVID-19 history had higher levels of T-helper cells (Th) when compared to COVID-19 naïve patients with sarcoidosis, but lower levels when compared to healthy controls. In COVID-19 convalescent patients with sarcoidosis, we noted higher absolute numbers and percentages of CD45RA–CCR7– and CD45RA+CCR7– cells within Th subset. Among COVID-19 convalescent patients with sarcoidosis we also found higher levels of T helper 1 cells and T helper 2 cells (with CXCR5–CCR6–CXCR3+CCR4– and CXCR5–CCR6–CXCR3–CCR4+ phenotypes, respectively) when compared to other groups. We also noted a statistically significant increase in central memory CXCR5+CCR6–CXCR3– follicular Th cells, as wells as effector memory CXCR5+CCR6–CXCR3– and CXCR5+CCR6+CXCR3– follicular Th cells in both groups of patients with sarcoidosis vs. healthy controls.ConclusionsOur study demonstrated Th cells imbalance in patients with sarcoidosis and COVID-19 history. These findings suggest possible clinical and visual progression of chronic lung sarcoidosis in COVID-19 convalescent patients.